RENU2 UV PMT Observations of the Cusp. Issue 20 (19th October 2020) - Fritz, Bruce A.; Lessard, Marc R.; Dymond, Kenneth F.; Kenward, David R.; Lynch, Kristina A.; Hecht, James H.; Clemmons, James H.; Cook, Timothy; Chakrabarti, Supriya; Solomon, Stanley C.
Abstract: The Rocket Experiment for Neutral Upwelling 2 (RENU2) sounding rocket launched from the Andøya Space Center on 13 December 2015 into the dayside polar cusp. An ultraviolet photomultiplier tube (UV PMT) on the RENU2 payload was oriented to look up along the spin axis for emissions of neutral atomic oxygen above the payload. Data from the UV PMT have been compared to predicted auroral emissions calculated by the Global Airglow (GLOW) model. The comparison between GLOW calculations driven by RENU2 electron precipitation measurements and UV PMT data suggest enhanced neutral density in the cusp at altitudes above the RENU2 trajectory. Key Points: Elevated UV PMT signal relative to GLOW prediction indicates an enhanced neutral density population above the RENU2 trajectory Simple, low‐resource instruments like the RENU2 UV PMT can be a powerful diagnostic tool for thermospheric structure Physics‐based models like GLOW are useful for understanding dynamic behavior in the cusp